2021
DOI: 10.1101/2021.11.29.21266947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The immunogenicity and reactogenicity of four COVID-19 booster vaccinations against SARS-CoV-2 variants of concerns (Delta, Beta, and Omicron) following CoronaVac or ChAdOx1 nCoV-19 primary series

Abstract: The appropriate COVID-19 booster vaccine following inactivated or adenoviral vector COVID-19 vaccination is unclear. We evaluated the safety and immunogenicity of different booster vaccines, inactivated (BBIBP-CorV), chimpanzee adenoviral vector (ChAdOx1), or mRNA (BNT162b2 at full (30 µg), or half (15 µg) dose) in healthy adults who received 2-dose primary series of either inactivated vaccine (CoronaVac) or ChAdOx1 8-12 weeks earlier. Overall, the adverse events for all booster vaccines were mild and moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…These results are consistent with a previous study of BNT162b2 following CV after three months [6]. Previous studies assessing the use of the standard mRNA vaccine dose after the CV series [1,7] or three standard doses of BNT162b2 or mRNA-1273 [11] also demonstrated high neutralizing antibodies against the omicron variant. This aligns with another study reporting that the use of 15-μg-BNT162b2 as a booster dose elicited neutralizing activity against the SARs-CoV-2 delta and omicron variants [7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with a previous study of BNT162b2 following CV after three months [6]. Previous studies assessing the use of the standard mRNA vaccine dose after the CV series [1,7] or three standard doses of BNT162b2 or mRNA-1273 [11] also demonstrated high neutralizing antibodies against the omicron variant. This aligns with another study reporting that the use of 15-μg-BNT162b2 as a booster dose elicited neutralizing activity against the SARs-CoV-2 delta and omicron variants [7].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies assessing the use of the standard mRNA vaccine dose after the CV series [1, 7] or three standard doses of BNT162b2 or mRNA-1273 [11] also demonstrated high neutralizing antibodies against the omicron variant. This aligns with another study reporting that the use of 15-μg-BNT162b2 as a booster dose elicited neutralizing activity against the SARs-CoV-2 delta and omicron variants [7]. Nevertheless, a previous study of mRNA-1273 showed that a third standard dose (100 μg) elicited a stronger immune response than a third reduced dose (50 μg) [12].…”
Section: Discussionmentioning
confidence: 99%
“…The result revealed that heterologous boosters could induce the production of large amounts of antibodies against Delta and Omicron, compared with homologous boosters. 134 Therefore, obtaining heterologous boosters might be an effective strategy to increase the intensity and persistence of the immune response (Figure 4 ).…”
Section: Strategies Against the Omicron Variantmentioning
confidence: 99%
“…The SARS-CoV-2 Omicron variant identified in late 2021 was found to harbour 36 mutations in the spike protein which enable the virus to evade immunity induced by infection or vaccination. Many studies suggested that a booster dose is needed to protect against Omicron [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%